Antifungal studies of acetone crude extract from the tree barks of vatica odorata / Wan Zuraida Wan Mohd Zain, Neni Kartini Che Mohd Ramli and Shaari Daud - Wan Mohd Zain, Wan Zuraida; Che Mohd Ramli, Neni Kartini; Daud, Shaari (2008)
Bioactivities of the acetone crude extracts from the tree barks of Vatica odorata was investigated on antifungal activity. Four genus of fungal were tested for anti-fungal activity i.e Rhizoctonia solani, Fusarium sp, Pythium sp. and Phytophthora sp., the pathogens of vegetables. The in-vitro bioassay of this acetone extract against fungal revealed that there were inhibition zone occurred for four genus of fungal tested. This revealed that there were anti-fungal activities of crude extract against plant pathogens.